New withanolides from Physalis minima and their cytotoxicity against A375 human melanoma cells. Issue 38 (16th June 2020) - Zhang, Meng; Zhang, Bingyang; Guang, Chenxi; Jiang, Benke; He, Xinya; Cao, Shijie; Ding, Liqin; Kang, Ning; Chen, Lixia; Qiu, Feng
Abstract : The new withanolides physaminilide A–G (1–7 ), and two artificial withanolides (8–9 ) were isolated from Physalis minima . Compounds 2, 5 and 8 exhibited significant cytotoxicity towards human tumor cells. Abstract : Seven previously undescribed withanolides, namely physaminilide A–G (1–7 ), and two artificial withanolides (8–9 ), along with 10 known analogues (10–19 ) were isolated from Physalis minima . The structures were established by spectroscopic analysis, including NMR and electronic circular dichroism (ECD) data. Cytotoxicity of all the isolates was evaluated against A375 human melanoma cells. Compounds 2, 5, 8, 10, 11 and 15 exhibited significant cytotoxic activities with IC50 values in the range of 1.2–9.4 μM.